ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – X. Chemical differentiation among the massive cores in G9.62+0.19. Issue 3 (9th March 2022) - Peng, Yaping; Liu, Tie; Qin, Sheng-Li; Baug, Tapas; Liu, Hong-Li; Wang, Ke; Garay, Guido; Zhang, Chao; Chen, Long-Fei; Lee, Chang Won; Juvela, Mika; Li, Dalei; et al.
ABSTRACT: Investigating the physical and chemical structure of massive star-forming regions is critical for understanding the formation and early evolution of massive stars. We performed a detailed line survey toward six dense cores, named MM1, MM4, MM6, MM7, MM8, and MM11, in the G9.62+0.19 star-forming region resolved in Atacama Large Millimeter/submillimeter Array (ALMA) band 3 observations. Toward these cores, about 172 transitions have been identified and attributed to 16 species, including organic oxygen-, nitrogen-, and sulphur-bearing molecules and their isotopologues. Four dense cores, MM7, MM8, MM4, and MM11, are line-rich sources. Modelling of these spectral lines reveals that the rotational temperature lies in the range 72–115, 100–163, 102–204, and 84–123 K for MM7, MM8, MM4, and MM11, respectively. The molecular column densities are 1.6 × 10 15 –9.2 × 10 17  cm −2 toward the four cores. The cores MM8 and MM4 show a chemical difference between oxygen- and nitrogen-bearing species, i.e. MM4 is rich in oxygen-bearing molecules, while nitrogen-bearing molecules, especially vibrationally excited HC3 N lines, are mainly observed in MM8. The distinct initial temperatures at the accretion phase may lead to this N/O differentiation. Through analysing column densities and spatial distributions of O-bearing complex organic molecules (COMs), we found that C2 H5 OH and CH3 OCH3 might have a common precursor, CH3 OH. CH3 OCHO and CH3 OCH3 are likely chemically linked. In addition, the observed variation in HC3 N and HC5 N emission may indicate their different formation mechanisms in hot and cold regions.